Atrator pullback para uma equação de onda semilinear amortecida - Moreira, Estefani Moraes (2018)
In this work, we present some of the theories of semigroups and global attractors. Also, we present process of evolution and pullback attractors. Finally, we show the existence and regularity of the pullback attractor for the problem $u_{tt} +\beta(t)u_t = \Delta u + f(u)$ in a bounded smooth domain $ \Omega \subset \mathbb{R}^n$ with the Dirichlet boundary conditions, the damping $\beta:\mathbb{R}\longrightarrow (0,+\infty)$ is a suitable function and $f \in C^2(\mathbb{R})$ is a nonlinear function with a dissipative condition.